Vertebrate Bistable Pigment Parapinopsin: Implications for Emergence of Visual Signaling and Neofunctionalization of Non-visual Pigment - Koyanagi, Mitsumasa; Kawano-Yamashita, Emi; Wada, Seiji; Terakita, Akihisa (Frontiers in Ecology and Evolution, 2017)
Opsins are light-sensor proteins, each absorbing a specific wavelength of light. This, in turn, drives a specific G protein-mediated phototransduction cascade, leading to a photoreceptor cell response. Recent genome projects have revealed an unexpectedly large number of opsin genes for vision and non-visual photoreception in various animals. However, the significance of this multiplicity of opsins remains largely unknown, except for that of cone visual opsins, which are diversified with respect to spectral sensitivity to achieve vertebrate color vision. Here, an implication of multiplicity is discussed, with focus on an ultraviolet-sensitive non-visual opsin—parapinopsin—that underlies pineal wavelength discrimination in lower vertebrates. Parapinopsins are phylogenetically close to vertebrate visual opsins, which have bleaching properties, but interestingly, parapinopsins are bleach-resistant bistable pigments, which photo-convert to stable photoproducts that revert to their original dark state by subsequent light absorption, similar to invertebrate rhodopsins. The unique characteristics of parapinopsin as an evolutionary intermediate between bistable and bleaching pigments provide insight into the evolutionary transition between signaling molecules that interact with two types of opsin-based pigments. Furthermore, the parapinopsin gene was duplicated in the teleost lineage and the spectral sensitivities of the duplicated parapinopsins were different from each other. On the basis of these results, together with the histochemical findings of parapinopsin, a plausible link between the diversification of a non-visual opsin parapinopsin and diverse pineal functions, wavelength discrimination, and melatonin secretion, implying why multiple opsins exist in animals, is proposed.